ANALISIS KESALAHAN PESERTA DIDIK BERDASARKAN NEWMAN’S ERROR ANALYSIS PADA KEMAMPUAN PEMECAHAM MASALAH MATEMATIS PESERTA DIDIK - Hidayati, Novira (Departemen Matematika, 2023)
Math matters in many spheres of life. Mathematical learning emphasizes problem-solving. Students must master problem-solving skills, which are vital in math and other professions. The mathematical problem-solving skill of kids should be mastered is not reality. Students still make numerous problem-solving blunders, thus they must be analyzed. This research employs the Newman Error method to identify student errors and their causes. Newman's technique categorizes mistakes as reading, comprehension, transformation, process skills, and final response writing. The research is descriptive qualitative. Six students from class IX SMP Negeri 15 Padang in 2023/2024 were interviewed for this research. Test results, interviews, data presentation, and verification. The proportion of pupils' reading and comprehending faults was 83.0%, which was quite high. Transformation error of 87.5% is pretty high. Very high process skill mistake of 95.5%. Very high final answer writing mistake of 96.3%.Keywords– Error Analysis, Newman Error Analysis, Problem Solving Ability, Mathematics